2008
DOI: 10.1007/s10238-008-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between rs5498 polymorphism in the ICAM1 gene and traditional risk factors influence susceptibility to coronary artery disease

Abstract: Coronary artery disease (CAD) depends on multiple genetic and environmental factors. Adhesion molecules are markers of endothelium dysfunction. Intercellular adhesion molecule-1 (ICAM-1) interacts with leukocyte integrins and promotes atherosclerotic process at the surface of endothelial cells. The aim of the study was to assess the association between ICAM1 rs5498 polymorphism and CAD and to establish whether there are any interactions between this polymorphism and traditional risk factors in determining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“…However, Grigg et al found that the soluble ICAM1 level of bronchoalveolar lavage was markedly higher in children whose parents smoked than in those whose parents did not [37]. Sarecka-Hujar et al reported a synergistic interaction between the rs5498 genotype and smoking that affected the risk of coronary artery disease [38]. All of these results support the present findings.…”
Section: Discussionsupporting
confidence: 87%
“…However, Grigg et al found that the soluble ICAM1 level of bronchoalveolar lavage was markedly higher in children whose parents smoked than in those whose parents did not [37]. Sarecka-Hujar et al reported a synergistic interaction between the rs5498 genotype and smoking that affected the risk of coronary artery disease [38]. All of these results support the present findings.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, our study could not reveal an association of ICAM-1 rs5498 with CAD significantly. In agreement with this finding, no significant difference was also observed in the distribution of rs5498 genotypes in ICAM-1 gene between cases and controls by another study 26. A number of SNPs may be silent with no direct effect on gene products.…”
Section: Discussionsupporting
confidence: 79%
“…Cybulsky [39] and colleagues also found that deficiency of VCAM-1 significantly diminishes early foam cell lesion formation throughout the aorta of Ldlr -/-mice. ICAM-1 has a similar structure, function, and expression patterns with VCAM-1; it plays a pivotal role in lymphocyte migration and activation and is considered important in the pathogenesis of atherosclerosis by compensate for VCAM-1 or cooperate with it in various inflammatory conditions [40] . The mechanisms of the proinflammatory effects of ICAM-1 on endothelial cells might be that ICAM-1 binds and interacts with leukocyte integrin receptors such as lymphocyte function-associated antigen-1 LFA-1 and Mac-1 [41] .…”
Section: Discussionmentioning
confidence: 99%